# Solve for v -7/3v=21 -73v=21
Multiply both sides of the equation by -37.
-37⋅(-73)⋅v=-37⋅21
Simplify both sides of the equation.
Simplify -37⋅(-73)⋅v.
Cancel the common factor of 3.
Move the leading negative in -37 into the numerator.
-37⋅(-73)⋅v=-37⋅21
Move the leading negative in -73 into the numerator.
-37⋅-73⋅v=-37⋅21
Factor 3 out of -3.
3(-1)7⋅-73⋅v=-37⋅21
Cancel the common factor.
3⋅-17⋅-73⋅v=-37⋅21
Rewrite the expression.
-17⋅-7⋅v=-37⋅21
-17⋅-7⋅v=-37⋅21
Cancel the common factor of 7.
Factor 7 out of -7.
-17⋅(7(-1))⋅v=-37⋅21
Cancel the common factor.
-17⋅(7⋅-1)⋅v=-37⋅21
Rewrite the expression.
-1⋅-1⋅v=-37⋅21
-1⋅-1⋅v=-37⋅21
Multiply.
Multiply -1 by -1.
1⋅v=-37⋅21
Multiply v by 1.
v=-37⋅21
v=-37⋅21
v=-37⋅21
Simplify -37⋅21.
Cancel the common factor of 7.
Move the leading negative in -37 into the numerator.
v=-37⋅21
Factor 7 out of 21.
v=-37⋅(7(3))
Cancel the common factor.
v=-37⋅(7⋅3)
Rewrite the expression.
v=-3⋅3
v=-3⋅3
Multiply -3 by 3.
v=-9
v=-9
v=-9
Solve for v -7/3v=21

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top